Interobserver variability of CT angiography for evaluation of aortic annulus dimensions prior to transcatheter aortic valve implantation (TAVI) - Schmidkonz, Christian; Marwan, M.; Klinghammer, Lutz; Mitschke, M.; Schuhbaeck, A.; Lell, Michael; Achenbach, Susanne; Pflederer, T.; Arnold, Martin (European Journal of Radiology, 2014)
Assessment of aortic annulus dimensions prior to transcatheter aortic valve implantation (TAVI) is crucial for accurate prosthesis sizing in order to avoid prosthesis-annulus-mismatch possibly resulting in complications like valve dislodgement, paravalvular regurgitation or annulus rupture. Contrast-enhanced multidetector computed tomography allows 3-dimensional assessment of aortic annulus dimensions. Only limited data exist about its interobserver variability.In 100 consecutive patients with symptomatic severe aortic stenosis (51 male, BMI 27±5kg/m(2), age 81±7 years, heart rate 72±15bpm, Logistic Euroscore 31±14%, STS-Score 7±4%), pre-interventional aortic annulus assessment was performed by dual source computed tomography (collimation 2×128×0.6mm, high pitch spiral data acquisition mode, 40-60ml contrast agents, radiation dose 3.5±0.9mSv). The following aortic annulus characteristics were determined by three independent observers: aortic annulus maximum, minimum and mean diameters (Dmax, Dmin, Dmean), eccentricity index (EI), effective aortic annulus diameter according to its circumference (Dcirc), effective aortic annulus diameter according to its area (Darea), distance from the aortic annulus plane to the left (LCA) and right coronary artery (RCA) ostia, maximum (DmaxAR) and minimum aortic root diameter (DminAR), maximum (DmaxSTJ) and minimum diameter of the sinotubular junction (DminSTJ). Subsequently, interobserver variabilities were assessed.Correlation between the three observers showed moderate to close agreement (between r=0.67 and r=0.97, all p<0.001). Mean differences (SE) between the three observers ranged from 0.07 (0.06)mm to 0.24 (0.07)mm for assessing the mean AA diameter (Dmean), from 0.28 (0.04)mm to 0.60 (0.06)mm for determining the effective AA diameter derived from the annulus area (Darea) and from 0.03 (0.07)mm to 0.07 (0.11)mm derived from the AA perimeter (Dcirc). For measurements of LCA and RCA distances to the AA level, mean interobserver differences (SE) ranged from 0.36 (0.07)mm to 0.76 (0.09)mm and from 0.15 (0.06)mm to 0.45 (0.11)mm.Computed tomography provides reproducible measurements of the aortic annulus and root geometry in patients scheduled for TAVI. The perimeter-derived aortic annulus diameter shows the lowest interobserver differences. Interobserver variabilities in prosthesis size recommendation were further reduced, if all three sizing methods were considered and stated as a "consensus result".
EVALuna2:11956